Xin hỏi 1 câu .
Tìm x : (x-3)4-(x+3)4=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =>2x>-6
hay x>-3
e: =>(5-x)/x<0
=>0<x<5
h: \(\Leftrightarrow\dfrac{x+5-x-3}{x+3}< 0\)
\(\Leftrightarrow x+3< 0\)
hay x<-3
g: \(\Leftrightarrow\dfrac{2x+7}{x+4}>0\)
\(\Leftrightarrow\left[{}\begin{matrix}x>-\dfrac{7}{2}\\x< -4\end{matrix}\right.\)
Câu 1 : \(-a.\left(c-d\right)-d.\left(a+c\right)=-c.\left(a+d\right)\)
Ta có : \(VT=-a.\left(c-d\right)-d\left(a+c\right)\)
\(=-ac+ad-da-dc\)
\(=-ac-dc\)
\(=-c\left(a+d\right)=VP\)
\(\Rightarrow-a\left(c-d\right)-d\left(a+c\right)=-c\left(a+d\right)\left(đpcm\right)\)
Câu 2 :
1, \(x.\left(x+7\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x+7=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=-7\end{cases}}}\)
2, \(\left(x+12\right)\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+12=0\\x-3=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-12\\x=3\end{cases}}}\)
3, \(\left(-x+5\right)\left(3-x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}-x+5=0\\3-x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=5\\x=3\end{cases}}}\)
4, \(x\left(2+x\right)\left(7-x\right)=0\)
\(\Rightarrow x=0;2+x=0\)hoặc \(7-x=0\)
\(\Rightarrow x=0;x=-2\)hoặc \(x=7\)
Ta có: lx-1l + l4-xl = 3 <=> lx-1l + lx-4l = 3
TH1: Nếu x < 1, ta có: TH2: Nếu 1 < x < 4, ta có: TH3: Nếu x > 4, ta có: 1 - x + 4 - x = 3 x - 1 + 4 - x = 3 x - 1 + x - 4 = 3 <=>5 - 2x = 3 <=> 3 =3 (TM) <=> 2x - 5 = 3
<=> 2x = 5 - 3 = 2 <=> x = 1;2;3;4 <=> 2x = 3 + 5 = 8 <=> x = 1 (TM) < => x = 4(TM) Vậy x = 1;2;3;4.
a:x=3/5-7/8=24/40-35/40=-11/40
b: =>1/3:(2x-1)=-1/6
=>2x-1=-2
=>2x=-1
=>x=-1/2
c: =>x-3/4=17/2+7/4=34/4+7/4=41/4
=>x=11
d: =>3x+2=0 hoặc 2/5x+7=0
=>x=-2/3 hoặc x=-7:2/5=-35/2
\(a,\dfrac{3}{2}\cdot x-1=\dfrac{1}{2}x-\dfrac{3}{5}\)
\(\Rightarrow\dfrac{3}{2}x-\dfrac{1}{2}x=-\dfrac{3}{5}+1\)
\(\Rightarrow\left(\dfrac{3}{2}-\dfrac{1}{2}\right)x=-\dfrac{3}{5}+\dfrac{5}{5}\)
\(\Rightarrow x=\dfrac{2}{5}\)
\(b,\dfrac{1}{2}x+\dfrac{1}{2}\left(x-2\right)=\dfrac{3}{4}-2x\)
\(\Rightarrow\dfrac{1}{2}x+\dfrac{1}{2}x+2x-1=\dfrac{3}{4}\)
\(\Rightarrow\left(\dfrac{1}{2}+\dfrac{1}{2}+2\right)x=\dfrac{3}{4}+1\)
\(\Rightarrow3x=\dfrac{7}{4}\)
\(\Rightarrow x=\dfrac{7}{4}:3\)
\(\Rightarrow x=\dfrac{7}{12}\)
\(c,\left(x-\dfrac{1}{2}\right)-\dfrac{1}{4}=0\)
\(\Rightarrow x-\dfrac{1}{2}=\dfrac{1}{4}\)
\(\Rightarrow x=\dfrac{1}{4}+\dfrac{1}{2}\)
\(\Rightarrow x=\dfrac{1}{4}+\dfrac{2}{4}\)
\(\Rightarrow x=\dfrac{3}{4}\)
\(d,4^{x-3}+1=17\)
\(\Rightarrow4^{x-3}=17-1\)
\(\Rightarrow4^{x-3}=16\)
\(\Rightarrow4^{x-3}=4^2\)
\(\Rightarrow x-3=2\)
\(\Rightarrow x=2+3\)
\(\Rightarrow x=5\)
#Toru
`3/2 x -1 =1/2x -3/5`
`=> 3/2x -1/2x = -3/5 +1`
`=> 2/2x= -3/5 + 5/5`
`=> x= 2/5`
__
`1/2x +1/2(x-2) = 3/4 -2x`
`=> 1/2x + 1/2x - 2/2 = 3/4 -2x`
`=> 1/2x +1/2x +2x = 3/4 + 1`
`=> 1/2x +1/2x + 4/2x = 3/4 +4/4`
`=> 6/2x = 7/4`
`=> x= 7/4 : 3`
`=>x=7/12`
__
`(x-1/2) -1/4=0`
`=> x-1/2=1/4`
`=> x=1/4 +1/2`
`=> x= 1/4 +2/4`
`=>x=3/4`
__
`4^(x-3) +1=17`
`=> 4^(x-3) =17-1`
`=> 4^(x-3)=16`
`=> 4^(x-3)=4^2`
`=> x-3=2`
`=>x=2+3`
`=>x=5`
(x - 3)4 - (x + 3)4 = 0
\(\Leftrightarrow\)[(x -3)2 - (x + 3)2 ]. [(x - 3)2 + (x + 3)2 ] = 0
\(\Leftrightarrow\)(x - 3 - x - 3)(x - 3 + x + 3)[(x - 3)2 + (x + 3)2 ] = 0
\(\Leftrightarrow\)-12x [(x - 3)2 + (x + 3)2 ] = 0
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=0\\\left(x-3\right)^2+\left(x+3\right)^2=0\end{cases}}\)
Xét: (x - 3)2 + (x + 3)2 = 0
Ta thấy \(\hept{\begin{cases}\left(x-3^2\right)\ge0\\\left(x+3\right)^2\ge0\end{cases}}\)\(\Leftrightarrow\)(x - 3)2 + (x + 3)2 \(\ge\)0
Dấu "=" xảy ra khi \(\hept{\begin{cases}x-3=0\\x+3=0\end{cases}}\)\(\Leftrightarrow\)\(\hept{\begin{cases}x=3\\x=-3\end{cases}}\)vô lý
Vậy x = 0
\(=\left(x-3+x+3\right)\left(x-3-x-3\right)=2x\left(-6\right)\)
\(=-12x\)